Oxidation State Roulette:Synthesis and Reactivity of Cobalt Complexes Containing SNS Ligands - Fitchett, Brandon (Université d'Ottawa / University of Ottawa, 2018)
The use of rare and expensive noble metals in the chemical industry as organometallic catalysts has grown exponentially in the past few decades due to their high activity, selectivity and their ability to catalyze a wide range of reactions. With this growth in use has also come a proportional growth in concern as these toxic metals inevitably leach into the environment and their negative effects on public health and our ecosystems are becoming better understood. First-row transition metal catalysts provide both environmental and economic benefits as alternatives to these noble metals due to their lower toxicity and cheaper costs. The two-electron chemistry that makes the noble metals so attractive however, is more challenging to accomplish with first-row transition metals. Intelligently designing the ligand scaffold which surrounds the metal can mitigate or even eliminate some of the shortfalls of these first-row metals. Some key features that should be considered when designing a ligand are: 1) a strong chelating ability so the ligand can stay attached to the metal, 2) incorporation of strong donors to favour low-spin complexes, 3) inclusion of hemilabile groups to allow for substrate activation and metal stabilization throughout various oxidation states, 4) redox activity to be able to donate or accept electrons, and 5) inclusion of Lewis base functionalities which are able to assist the substrate activation. Ligands which incorporate these features are known as bifunctional ligands as they can accomplish more than one function in the catalytic cycle. Developing first-row transition metal complexes containing these ligands may enable these species to replicate the reactivity and selectivity generally associated with the precious metals. Being able to replace the noble metals used in industry with these catalysts would have tremendous environmental and economic benefits. The objective of this thesis is to advance the field of bifunctional catalysis by examining the behaviour of two sterically svelte, tridentate SNS ligands containing hard nitrogen and soft sulphur donors when bonded to cobalt. Previous work with iron provides a template of the ligand behaviour to which cobalt can be compared, allowing us to contrast the effects exerted by the different metals. After an introduction to bifunctional catalysis in Chapter 1, Chapter 2 describes the reactivity of the amido ligand, SMeNHSMe, with precursors ranging from Co(I) to Co(III), all of which yielded the 19e- pseudooctahedral cobalt(II) bis-amido complex, Co(SMeN-SMe)2 characterized by 1H NMR spectroscopy, single-crystal X-ray crystallography and cyclic voltammetry. Although this complex has a similar structure as the Fe analogue, the cobalt bis-amido complex did not exhibit the same hemilabile behaviour that allowed for simple ligand substitution of one of the thioether groups. Instead it reacted reversibly with 2,2’-bipyridine while 1,2-bis(dimethylphosphino)ethane (DMPE) and 2,6-dimethylphenyl isocyanide both triggered additional redox chemistry accompanied by the loss of protonated SMeNHSMe. In contrast, protonation gave the cobalt(II) amido-amine cation, [Co(SMeNSMe)(SMeNHSMe)](NTf2), which allowed for substitution of the protonated ligand by acetonitrile, triphenylphosphine and 2,2’-bipyridine based on 1H NMR evidence. The ability of Co(SMeNSMe)2 to act as a precatalyst for ammonia-borane dehydrogenation was also probed, revealing that it was unstable under these conditions. Addition of one equivalent of DMPE per cobalt, however, resulted in better activity with a preference for linear aminoborane oligomers using ammonia-borane and, surprisingly, to a change in selectivity to prefer cyclic products when moving to methylamine-borane. Chapter 3 delves into the chemistry of the thiolate ligand, SMeNHS, which formed a new 18e- cobalt(III) pseudooctahedral complex, Co(S-NC-)(SMe)(DEPE), from oxidative addition of the Caryl-SMe bond. Scaling up this reaction resulted instead in formation of an imine-coupled [Co(N2S2)]- anion which was characterized by 1H NMR/EPR spectroscopy, single-crystal X-ray diffraction, cyclic voltammetry and DFT studies. The latter revealed an interesting electronic structure with two electrons delocalized in the ligand, demonstrating the non-innocent nature of the N2S2 ligand. While the analogous iron complex proved to be an effective pre-catalyst for the hydroboration of aldehydes with selectivity against ketones, this behaviour was not observed with [Co(N2S2)]- which gave a slower rate and less selectivity. The knowledge acquired from this thesis work has advanced the field of bifunctional catalysis by extending the application of these two SNS ligands from iron to cobalt, revealing unpredictable differences in reactivity between the metals. By comparing the behaviour of these ligands with iron and cobalt, we gain a better understanding of the chemistry that is accessible by these ligands and the applications for which they may be used. This increased knowledge contributes to our long-term goal of replacing expensive and toxic noble metals with more benign first-row transition metals, improving the sustainability of the chemical industry.
Keywords: Bifunctional Catalysis; Cobalt SNS; Organometallics; Ligand Design